Math, asked by rinkupankaj78, 11 months ago

(iv) (a²- b²)(a² +b²) - (a² – b²)^2​

Answers

Answered by TakenName
1

Answer:

2b² (a + b) (a - b)

Step-by-step explanation:

There is a common divisor a^2-b^2.

  • ma+mb=m(a+b)

Let's solve the problem.

→(a² - b²) (a² + b²) - (a² - b²)²

=(a² - b²) (a² + b²) - (a² - b²) (a² - b²)

=(a² - b²) { (a² + b²) - (a² - b²) }

=(a² - b²) (a² + b² - a² + b²)

=(a² - b²) × 2b²

  • (a + b) (a - b) = a² - b²

→2b² (a + b) (a - b)

Answered by phananh4c001
0

Answer:

Step-by-step explanation:

(a²-b²)(a²+b²)=a⁴-b⁴=(a²)²-(b²)²

a⁴-b⁴-2(a²-b²)+1-1=[ (a²)²-2a²+1]-[(b²)²-2b²+1]

= (a²-1)²-(b²-1)²=(a²-b²-2)(a²+b²)

Similar questions